Asian Strategic Partnerships: New Practices and Regional Security Governance. Issue 1 (16th January 2016) - Envall, H. D. P.; Hall, Ian
Abstract : This article examines the use of strategic partnerships by Asian states as a means of enhancing national and regional security, as well as advancing economic and other objectives. It argues that strategic partnerships are best conceived as a new practice that signals the emergence of new forms of "security governance" in the region. It observes, however, that whereas early strategic partnerships were based on substantive shared agreement on "system principles, " contemporary strategic partnerships take different forms, some grounding closer cooperation between like‐minded partners and some intending to facilitate better management of partners with divergent values and interests. The contemporary behavior of the United States and its traditional and new security partners in the region conform to this general pattern. The article concludes that the proliferation of strategic partnerships and the emergence of regional security governance should prompt a reappraisal of traditional approaches to Asian security, which tend to concentrate on architecture and community at the expense of practices.